Announcements of changes in dividend payments and their impact on shareholders' wealth: empirical evidence in Chile - Maquieira V., Carlos; Osorio M., Desiré (Estudios de Administración, 2000)
The following is the first study in documenting the impact of significant changes in dividend payments on shareholders’ wealth in Chilean companies. The sample consists of 129 changes in dividend payments (75 increases and 59 decreases) above or below a real change of 10%. The study period goes from 1990 to 1995. The cumulative abnormal returns for two days around the dividend announcement date are 1.11% and –1.19% for increases and decreases, respectively. These results are statistically significant. Furthermore, we only find significant abnormal returns for definitive dividend announcements. Finally, we also report significant CAR for 10 days around the dividend announcement date, for which we do not have an economic explanation.